Effect of various malocclusion on maximal bite force- a systematic review - Harneet Kaur; Neelam Singh; Harshita Gupta; Ankita Chakarvarty; Pushpjot Sadana; Natasha Gupta; Anuraj Kochhar; Ritasha Bhasin (Journal of Oral Biology and Craniofacial Research)
Objective: This systematic review evaluates the variation in molar bite force (MBF) with the type and severity of dental malocclusion in young adults with permanent dentition. Methods: We searched seven electronic databases until December 31, 2021, and identified 1898 articles, of which 22 full-texts were reviewed. Eight clinical studies with subjects having permanent dentition with various dental malocclusions and quantifying maximal bite force were included for the review. Newcastle Ottawa scale was used to assess the risk of bias and GRADE to study the certainty of evidence. Articles were evaluated for the primary outcome (variation of MBF in different malocclusion groups) and confounding factors affecting MBF. Results: All studies measured MBF in individuals with normal and malocclusion, with 2329 subjects having permanent dentition. A positive correlation of Class I normal occlusion with the bite force was seen compared to Class II and III malocclusion. Unilateral crossbite patients had lesser bite force. Six studies with 1023 males and 1175 females showed MBF more in males than females. In 3 studies (332 subjects), no significant difference for MBF between the right and left sides of the jaws was measured. Conclusion: MBF decreases significantly with vertical and transverse craniofacial and dental discrepancy. Normal sagittal occlusion has more molar bite force than patients with different malocclusions. Also, MBF is more in males than females, and it increases with age. Registration: PROSPERO CRD42021249328.